The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25153525
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of the Biomass Torrefaction Process on Selected Parameters of Dust Explosivity

Abstract: This article presents the findings of a study investigating the explosion and combustion parameters of dust from the raw biomass of wheat straw and energy willow and from the products of biomass torrefaction generated at temperatures ranging from 220 to 300 °C. Agricultural waste and energy crops and their modifications, e.g., in the torrefaction process, did not find a place in explosive risk research, which the authors decided to present in their work. The study was designed to estimate explosion hazard duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(39 reference statements)
4
5
0
Order By: Relevance
“…Pyrolysis leads to higher carbon concentrations and volatile contents and results in the increased brittleness of the thermally processed products. A similar relationship was reported by Bajcar et al (2020), who assessed the dust explosivity in the raw biomass of wheat straw and energy willow and in products of the torrefaction process applied to those materials. The authors observed that Pmax increased by a maximum of 28% with a higher torrefaction process temperature [47].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Pyrolysis leads to higher carbon concentrations and volatile contents and results in the increased brittleness of the thermally processed products. A similar relationship was reported by Bajcar et al (2020), who assessed the dust explosivity in the raw biomass of wheat straw and energy willow and in products of the torrefaction process applied to those materials. The authors observed that Pmax increased by a maximum of 28% with a higher torrefaction process temperature [47].…”
Section: Discussionsupporting
confidence: 77%
“…A similar relationship was reported by Bajcar et al (2020), who assessed the dust explosivity in the raw biomass of wheat straw and energy willow and in products of the torrefaction process applied to those materials. The authors observed that Pmax increased by a maximum of 28% with a higher torrefaction process temperature [47]. Półka (2020) reported a maximum explosion pressure for coke dust amounting to 6.84 bar.…”
Section: Discussionsupporting
confidence: 77%
“…Bajcar et al showed an increase in the explosion index K st max , which, in the case of raw willow biomass, was estimated at the level of 72 bar s −1 , and for the torrefied material amounted to 81 bar s −1 . A similar tendency was identified in the case of wheat straw; the dust explosion index K st max of raw biomass amounted to 55 bar s −1 , and with the torrefied materials it increased to 62 bar s −1 [ 143 ]. Saletnik et al classified the thermally unprocessed oak, coniferous pellets and their mixture, as well as the thermally processed forms obtained from them, into the first class of dust explosion hazard (St1)—a material not susceptible to explosiveness.…”
Section: Resultssupporting
confidence: 66%
“…The thermal processes leads to an increased concentration of carbon, higher contents of volatile substances, and greater brittleness observed in the materials after thermal treatment. Despite the visible trend, these differences are not significant and do not result in a change of dust classification [ 143 ]. According to Cashdollar, Cordero et al and Demirbas, as well as other researchers, the differences between raw and thermally processed biomass can mainly be explained by the different emissivity of the respective materials linked to the mechanisms of heat transfer [ 145 , 146 , 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the production of wood chips, wood dust often swirls in cloud concentrations, which, especially in combination with fuel vapors and engine heat, can create a dangerous explosive mixture that can endanger the life and health of workers, as well as cause damage to property and equipment [90,91].…”
mentioning
confidence: 99%